PERANCANGAN WEBSITE SHOWROOM MOBIL BERBASIS LARAVEL UNTUK EFISIENSI AKSES DAN UKURAN - Salfriandry, Radja Ravine (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
Abstract. In an increasingly competitive digital era, website performance is a crucial factor in determining service quality and user satisfaction. Access speed and file size efficiency are two main aspects that affect user experience in accessing an online platform. Based on these needs, a Laravel-based car showroom website design and development is carried out with a focus on reducing file size and increasing access speed, using a case study at ARR Motor showroom. The method used is the Agile approach with the Kanban model, which includes the stages of needs analysis, system design, implementation, testing, and evaluation. The optimization strategy applied includes image compression, lazy loading, caching, and database query optimization through eager loading techniques. Test results with Laravel Debugbar and User Acceptance Test (UAT) showed a significant improvement in the efficiency of load time and system resource usage. These findings show that the application of optimization techniques in the Laravel framework can produce an efficient, lightweight, and responsive showroom website.